HUBUNGAN ANTARA KARAKTERISTIK MATERNAL DENGAN KEJADIAN STUNTING PADA BALITA DI POSYANDU KENANGA 1 WILAYAH PUSKESMAS CILANDAK BARAT: Tara Nur Fadilah, Sri Dinengsih, Risza Choirunissa - Tara Nur Fadilah (STIKES MITRA RIA HUSADA, 2021)
Introduction: stunting is a chronic condition that depicts growth due to long-term malnutrition.The incidence of stunting (short) toddlers is the main nutritional problem facing Indonesia.Based on the nutritional Status monitoring (PSG) data for the last three years, short has thehighest prevalence compared to other nutritional issues such as lack of nutrition, lean, andobese. Prevalence of short infants increased from 27.5 2016 to 29.6% in 2017Method: This type of research is a type of observational analytic by using cross sectionalDesign Sample amount as much as 62 Toddlers sampling technique in totalsample.Independent variables are exclusive breast milk, knowledge,penuped, family income andmaternal nutritional Status and dependent variables are stunting events.Result: that of the cross-tabulation results showed that from 62 children who were stunted asmany as 33 (69.4%) who were not given exclusive breast milk while the exclusive of 39(62,9%) with the knowledge of less than 41 (66,1%). undereducated as much as 42(67,7%), The revenue of the unsuitable UMP 43 (69,4%). nutritional status of Mothers WITHKEK as much as 43 (69,4)Analysis : so that based on the test results using the program SPSS 22, 0 using the ChiSquare test, with a significant degree of significance α = 0.05 gained that there is asignificant relationship between education and the Stunting event with a value of p value0.000, There is a significant relationship between income and Stunting with the value of pvalue 0.000, there is a significant relationship between the nutritional Status and the Stuntingevent with the value of p value 0.000 and no relationship between the exclusive feedingwith the Stunting event with the value of p value 0.271, there is no relationship betweenknowledge with Stunting events with a value of p value 0.023,Discussion: Qualitative Then there is the relationship between education, income, andnutritional status with stunting events in the posyandu kenanga I Health Care areaCilandak Jakarta Selatan is recommended to increase The efforts of the incidence ofnutritional status during pregnancy through health education.